Global wildlife trade permeates the Tree of Life - Fukushima, Caroline Sayuri; Mammola, Stefano; Cardoso, Pedro (Biological conservation, 2020)
Legal and illegal wildlife trade is a multibillion dollar industry that is driving several species toward extinction. Even though wildlife trade permeates the Tree of Life, most analyses to date focused on the trade of a small selection of charismatic vertebrate species. Given that vertebrate taxa represent only 3% of described species, this is a significant bias that prevents the development of comprehensive conservation strategies. In this short contribution, we discuss the significance of global wildlife trade considering the full diversity of organisms for which data are available in the IUCN database. We emphasize the importance of being fast and effective in filling the knowledge gaps about non-vertebrate life forms, in order to achieve an in-depth understanding of global trading patterns across the full canopy of the Tree of Life, and not just its most appealing twig. •Global wildlife trade is a multibillion dollar industry that is driving several species toward extinction.•Most analyses on global wildlife trade are biased toward vertebrates.•Multiple datasets suggest that a huge fraction of illegal and legal traded wildlife is plant and invertebrates.•It is fundamental to fill this knowledge gap about global trade of non-vertebrate life forms.